2012
DOI: 10.1021/cg201661y
|View full text |Cite
|
Sign up to set email alerts
|

Anticaking Activity of Ferrocyanide on Sodium Chloride Explained by Charge Mismatch

Abstract: Sodium chloride crystals have a strong tendency to cake, which can be prevented by treating them with the anticaking agent ferrocyanide. Using surface X-ray diffraction, we show how the ferrocyanide ion sorbs onto the {100} face of the sodium chloride crystal where it replaces a sodium ion and five surrounding chloride ions. The coverage is about 50%. On the basis of the determined atomic structure, we propose the following anticaking mechanism. Because of the charge of the ferrocyanide ions sorbed on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“…Some crystallization inhibitors, such as hexacyanoferrate, are known to promote noncrusting salt efflorescence rather than the destructive crusting efflorescence and subflorescence (i.e., salt nucleation and crystallization within pores) in ridged porous media such as building materials and industrial infrastructures (Gupta et al, 2012; Nachshon et al, 2011; Fujimaki et al, 2006; Selwitz and Doehne, 2002). The hexacyanoferrate ion geometry and size is similar to NaCl salt clusters that allow ion replacement and block salt crystallization via differences in ion charges (Bode et al, 2012). This leads to a supersaturated state that is diffusion limited as compared with the convective water flux supplying evaporation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some crystallization inhibitors, such as hexacyanoferrate, are known to promote noncrusting salt efflorescence rather than the destructive crusting efflorescence and subflorescence (i.e., salt nucleation and crystallization within pores) in ridged porous media such as building materials and industrial infrastructures (Gupta et al, 2012; Nachshon et al, 2011; Fujimaki et al, 2006; Selwitz and Doehne, 2002). The hexacyanoferrate ion geometry and size is similar to NaCl salt clusters that allow ion replacement and block salt crystallization via differences in ion charges (Bode et al, 2012). This leads to a supersaturated state that is diffusion limited as compared with the convective water flux supplying evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, subflorescence without a crystallization inhibitor occurs as massive cubic crystals, forming a hard crust within the medium's pores (Selwitz and Doehne, 2002). When a crystallization inhibitor limits salts from forming a cemented crust (i.e., blocking pores), but instead causes noncrusting efflorescence, the medium's convective water and salt transport maintained as a higher rate (Nachshon and Weisbrod, 2015; Shokri, 2014; Bode et al, 2012; Gupta et al, 2014; Nachshon et al, 2011; Fujimaki et al, 2006). Therefore, the efflorescence yields large amounts of salt in a period of just hours or days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to answer this question, we need to know the structure of FCN at the NaCl(100) surface. A carefully prepared (and flat) (100) surface with approximately 0.5 monolayer of FCN was subjected to an interface X-ray diffraction investigation [21]. The final model from this research is shown in Fig.…”
Section: Role Of Additives: Anti-caking Agents For Naclmentioning
confidence: 99%
“…39 NaCl dissolution is also of practical importance in relation to developing anticaking technologies in the food industry. 6,40,41 Since conductance measurements 42 have been widely used for dissolution studies on a macro-scale in suspensions, we envisage that the dual-barreled conductance micropipet described herein could be widely adopted for the study of dissolution (and growth) processes. More generally, the work in this paper further enhances a growing family of quantitative pipet-based imagining techniques.…”
Section: Introductionmentioning
confidence: 99%